Horizontally acquired AT-rich genes in Escherichia coli cause toxicity by sequestering RNA polymerase - Lamberte, L; Baniulyte, G; Singh, S; Stringer, A; Bonocora, R; Stracy, M; Kapanidis, A; Wade, J; Grainger, D (Springer Nature, 2017)
Horizontal gene transfer permits rapid dissemination of genetic elements between individuals in bacterial populations. Transmitted DNA sequences may encode favourable traits. However, if the acquired DNA has an atypical base composition, it can reduce host fitness. Consequently, bacteria have evolved strategies to minimize the harmful effects of foreign genes. Most notably, xenogeneic silencing proteins bind incoming DNA that has a higher AT content than the host genome. An enduring question has been why such sequences are deleterious. Here, we showed that the toxicity of AT-rich DNA in Escherichia coli frequently results from constitutive transcription initiation within the coding regions of genes. Left unchecked, this causes titration of RNA polymerase and a global downshift in host gene expression. Accordingly, a mutation in RNA polymerase that diminished the impact of AT-rich DNA on host fitness reduced transcription from constitutive, but not activator-dependent, promoters.